Lack of reliability of nanotechnology in the of free plasma DNA in samples of patients with prostate cancer - Moreno, Ricardo; Delgado, Pamela O; Coelho, Patrícia G; Marsicano, Sarah R; Boas, Viviane Av; Azzalis, Ligia A; Junqueira, Virgínia Bc; Rocha, Katya C; De Abreu, Luiz Carlos; Valenti, Vitor E [UNESP]; Drezzet, Jefferson; Pereira, Edimar Cristiano; et al. (Springer Nature, 2013)
Background: Several studies seek biological markers that give diagnostic and degree of tumor development. The aim of this study was to validate the determination of plasma DNA using nanotechnology (Nanovue™-NV) in samples of 80 patients with prostate cancer. Methods. Blood samples of 80 patients of the Urology Ambulatory of Faculdade de Medicina do ABC with prostate cancer confirmed by anatomical-pathology criteria were analyzed. DNA extraction was performed using a GFX TM kit (Amersham Pharmacia Biotech, Inc, USA) following the adapted protocol. Plasma was subjected to centrifugation. Results: There was a big difference between the first and the second value obtained by NanoVue Only two samples had no differences between duplicates. Maximum difference between duplicates was 38 μg/mL. Average variation between 51 samples was 10.29 μg/mL, although 21 samples had differences above this average. No correlation was observed between pDNA obtained by traditional spectrophotometry and by nanotechnology. Conclusion: Determination of plasma DNA by nanotechnology was not reproducible. © 2013 Moreno et al; licensee BioMed Central Ltd.
Keywords: DNA; Nanotechnology; Neoplams; Prostate; blood level; blood sampling; cancer patient; centrifugation; DNA determination; DNA extraction; human; major clinical study; male; nanotechnology; prostate cancer; reliability; spectrophotometry